Barthes and the Orient: Ethical Responsibility and Political Commitment - García Soto, Luís (Res Publica. Revista de Historia de las Ideas Políticas, 2022)
In this text, I deal with the relationship between the French Philosopher Roland Barthes (1915-1980) and the Orient. In his work, three different Orients can be found: Japan, China and Morocco. Barthes visited these three countries as a tourist, was a resident in Morocco for a year and wrote about their cultures. The Orient left several important traces in his writings and plays an important role in Barthes’s work. In my analysis, I examine Barthes’s views on Japan, China and Morocco, along with the criticism they deserved. In conclusion, I stress the ethical responsibility and political commitment that, in each case, Barthes assumes.
Keywords: Orient; Post-Colonialism; Intellectual; Commitment; Ethics